2019
DOI: 10.1186/s13046-019-1102-6
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ZEB1-AS1 regulates miR-200b/FSCN1 signaling and enhances migration and invasion induced by TGF-β1 in bladder cancer cells

Abstract: Background The effect of competing endogenous RNA (ceRNA) can regulate gene expression by competitively binding microRNAs. Fascin-1 (FSCN1) plays an important role in the regulation of cellular migration and invasion during tumor progression, but how its regulatory mechanism works through the ceRNA effect is still unclear in bladder cancer (BLCA). Methods The role of fascin-1, miR-200b , and ZEB1-AS1 in BLCA was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 49 publications
1
46
0
Order By: Relevance
“…As a result, the expression of the miR-200b target, fascin1, is induced in bladder cancer cells, leading to activated migration and invasion. Induced ZEB1-AS1 expression inhibits apoptosis, promotes the cell cycle, and activates proliferation, as well as stimulates the growth of bladder cancer xenografts in mice [296]. According to another study, miR-200b targets and inhibits the expression of MMP16.…”
Section: Bladder Cancermentioning
confidence: 98%
“…As a result, the expression of the miR-200b target, fascin1, is induced in bladder cancer cells, leading to activated migration and invasion. Induced ZEB1-AS1 expression inhibits apoptosis, promotes the cell cycle, and activates proliferation, as well as stimulates the growth of bladder cancer xenografts in mice [296]. According to another study, miR-200b targets and inhibits the expression of MMP16.…”
Section: Bladder Cancermentioning
confidence: 98%
“…Our recent work identified many differential lncRNA through TCGA database, and we revealed that ZEB1‐AS1 was significantly up‐regulated in ESCA, but its precise functions remain unknown. It is a fact that ZEB1‐AS1 is closely correlated with tumour occurrence and development, such as bladder cancer, glioma, melanoma and non–small‐cell lung cancer, and these data suggest that ZEB1‐AS1 is involved in tumour progression via multiple different molecular mechanisms, suggesting the complexity of ZEB1‐AS1 function in these tumours. However, how ZEB1‐AS1 is regulated during ESCC development is still unclear, and therefore, herein, the expression pattern of ZEB1‐AS1 and its regulatory role in the proliferation and invasion ability of ESCC were investigated, which will propose ZEB1‐AS1/ZEB1 regulatory axis as an underlying therapeutic target for ESCC therapy.…”
Section: Introductionmentioning
confidence: 82%
“…LncRNA FBXL19‐AS1 strengthens the breast cancer cells invasion and growth abilities by sponging miR‐718 . LncRNA ZEB1‐AS1 promotes TGF‐β1‐induced invasion of bladder tumor cells via targeting the miR‐200b/FSCN1 pathway . LINC00152 suppresses the development of esophageal carcinoma via sponging miR‐153‐3p and targeting FYN …”
Section: Introductionmentioning
confidence: 99%
“…15 LncRNA ZEB1-AS1 promotes TGF-β1-induced invasion of bladder tumor cells via targeting the miR-200b/FSCN1 pathway. 16 LINC00152 suppresses the development of esophageal carcinoma via sponging miR-153-3p and targeting FYN. 17 In this research, LINC00961 was downregulated in colon cancer.…”
mentioning
confidence: 99%